Mediating Legitimacy : Chieftaincy and Democratisation in Two African Chiefdoms. - Fokwang, Jude (Langaa RPCIG, 2009)
This study analyses the effects of democratic transition in two African countries - Cameroon and South Africa - on chiefs and the institution of chieftainship. Based on ethnographic fieldwork, the monograph explores the cultural and socio-political conditions that enabled chiefs to reinvent themselves in the new era of democratic politics despite their status as 'old political actors'. It explores the kinds of legitimacies claimed by chiefs in the new era and the responses of their subjects to such claims, particularly with respect to chiefs' involvement in national politics. The monograph mak.